2013
DOI: 10.5539/jas.v5n3p132
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Purification of Anti-Helicobacter pylori IgY

Abstract: The aim of this study was to establish an efficient procedure to produce anti-H. pylori urease IgY from the eggs of the laying hens. Four White Leghorn hens (52 weeks old) were immunized intramuscularly with the purified urease of H. pylori with aluminum hydroxide gel adjuvant. To increase the specificity and antibody titer, three boosters were given at 2-week intervals following the first injection. After the final immunization, the eggs were collected daily and stored at 4°C. The yield of yolk proteins were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Therefore, IgY is a potential substitute for antibiotics. Our previous study also indicated that the anti E. Coli and and Helicobacter pylori IgY can specific bind to the bacterias (Liou et al, 2010;Siriya et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, IgY is a potential substitute for antibiotics. Our previous study also indicated that the anti E. Coli and and Helicobacter pylori IgY can specific bind to the bacterias (Liou et al, 2010;Siriya et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The IgY from the egg yolks was extracted using ammonium precipitation and exchange chromatography methods, which are similar to methods that were described before in Ko et al's, Shin et al's and Siriya et al's studies 14,21,22 . First, the yolks were separated from the white and homogenized until it turned into a suspension.…”
Section: Isolation and Purification Of Igymentioning
confidence: 99%
“…On the other hand, Siriya et al [55] spot more light on the economic point of view. They applied a study aimed to establish an efficient procedure to produce anti-H. pylori urease IgY from the eggs of the laying hens.…”
Section: Anti-h Pylori Urease Igymentioning
confidence: 99%